2018
DOI: 10.1017/s1751731117003123
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the physical, technological and economic factors driving the intensification trajectories of livestock systems

Abstract: Over the past 100 years, the French livestock sector has experienced significant intensification that has occurred in different ways across the country. Specifically, France has changed from a homogeneous state with most of the agricultural area covered by grasslands and a uniform distribution of animals, to a heterogeneous state characterised by an uneven distribution of grasslands, livestock numbers and livestock species. Studying the dynamics of this change is fundamental to the identification of drivers th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 34 publications
0
7
0
4
Order By: Relevance
“…La figure 1 montre les principaux flux calculés. Des analyses de flux de l'élevage français montrent une forte intensification de l'élevage combinée à une bonne autonomie en fourrage et un déficit en concentrés principalement en tourteaux (Dourmad et al, 2017 ;Domingues et al, 2018). À l'échelle des petites régions agricoles ces travaux montrent de fortes hétérogénéités des productions animales et des autonomies alimentaires suggérant des échanges nationaux et internationaux importants donc une ouverture des cycles de nutriments (Dourmad et al, 2017).…”
Section: L'écologie Territorialeunclassified
“…La figure 1 montre les principaux flux calculés. Des analyses de flux de l'élevage français montrent une forte intensification de l'élevage combinée à une bonne autonomie en fourrage et un déficit en concentrés principalement en tourteaux (Dourmad et al, 2017 ;Domingues et al, 2018). À l'échelle des petites régions agricoles ces travaux montrent de fortes hétérogénéités des productions animales et des autonomies alimentaires suggérant des échanges nationaux et internationaux importants donc une ouverture des cycles de nutriments (Dourmad et al, 2017).…”
Section: L'écologie Territorialeunclassified
“…Les transformations au niveau national ne se sont pas déployées de façon homogène sur l'ensemble des départements. Le processus d'intensification de l'élevage s'est spatialement différencié au cours du temps (Domingues et al, 2018). Ces auteurs synthétisent cette différenciation spatiale en mobilisant une analyse multivariée de données qui permet i) de retirer l'effet absolu Domingues et al, 2018 ;d'après Cavailhès et al, 1987).…”
Section: Intensification Au Niveau Des Départementsunclassified
“…The system boundary defined in this study is the French administrative entity called a 'department', equivalent to the NUTS3 level of the classification of the economic territory of Europe. The choice of 48 departments (out of a total 88) relies on the results of Domingues et al (2018) that identified trajectories of intensification, among which are these 48 departments where livestock plays a major role.…”
Section: The Socioecological Metabolism Of Livestock Areasmentioning
confidence: 99%
“…The six indicators presented above were computed for a set of 48 departments in the main livestock areas (Domingues et al 2018). In order to analyse possible interactions, we used pairwise comparison, which for the set of six indicators, combined two by two, resulted in a total of 15 interactions.…”
Section: Nitrogen Excretion Emissionsmentioning
confidence: 99%